COMPARISON OF EFFECTIVENESS OF INFERIOR ALVEOLAR NERVE BLOCK AND GOW GATES TECHNIQUE IN MANDIBULAR MOLAR TEETH WITH IRREVERSIBLE PULPITIS - Aabbasi, Abeera Faraz; Rizwan Qureshi,; Shazia Mehmood,; Ghazala Dayyan,; Muhammad Adnan Rashid,; Saqib Sarfaraz, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Local anaesthetics are the most important and most utilized agents in the dental profession today. Achieving effective pain control holds a prime importance for any dental procedure. The most commonly employed technique to achieve effective anaesthesia in mandibular molar teeth with irreversible pulpitis is Inferior Alveolar Nerve Block. However, in some cases this technique may not prove successful and the clinician may have to resort to alternative methods of achieving effective anaesthesia. Our study aims to compare two different techniques employed for anaesthesia, i.e., the conventional Inferior Alveolar Nerve Block and the alternative Gow Gates Technique in achieving effective anaesthesia in mandibular molar teeth. Methods: We conducted a randomized controlled trial in the Operative Dentistry department of Rawal Institute of Health Sciences Islamabad. We selected 102 patients presenting with irreversible pulpitis in mandibular posterior teeth. The selected patients were randomly allocated into two groups. In each group, the subjects were given 1.8 m.L of lidocaine (2%) with epinephrine 1: 100,000 (Medicainer Inj, HuonCo., Ltd, Korea) by using anaesthetic cartridges that had aspirating syringe. Results: Subjects in Group A were given inferior alveolar nerve block while those in Group B received Gow-Gates nerve block. The patients were then asked to rate their pre-operative and intra-operative pain on a visual analogue scale (VAS). Data analysis was done using SPSS-22, followed by comparison of efficacy between the two groups. anaesthesia was found to be effective among 36 subjects (69%) of Group-A and 44 subjects of (84%) Group-B. Hence, we concluded that the success rate of Gow-Gates technique and Inferior alveolar nerve block anaesthetic technique differs significantly. Conclusion: Gow-Gates technique can be considered as an applicable alternative to the conventional Inferior alveolar nerve block technique while providing anaesthesia to patients presenting with irreversible pulpitis in mandibular posterior teeth, having a higher anaesthetic success of (84%) when compared with the conventional Inferior alveolar nerve block (69%).